In vitro and in vivo antioxidant therapeutic evaluation of phytochemicals from different parts of Dodonaea viscosa Jacq - Khan, Siraj; Rehman, Mujeeb Ur; Khan, Muhammad Zafar Irshad; Kousar, Rehana; Muhammad, Khan; Haq, Ihsan Ul; Ijaz Khan, Muhammad; Almasoud, Najla; Alomar, Taghrid S.; Rauf, Abdur (Frontiers in Chemistry, 2023)
Natural antioxidants are vital to promote health and treat critical diseased conditions in the modern healthcare system. This work adds to the index of natural medicines by exploring the antioxidant potential of Dodonaea viscosa Jacq. (Plant-DV). The aqueous extract of leaves and seeds from plant-DV in freshly prepared phosphate buffer is evaluated for antioxidant potential. In vitro antioxidant potential of the nascent and oxidatively stressed extracts was analyzed through glutathione (GSH) assay, hydrogen peroxide (H2O2) scavenging effect, glutathione-S-transferase (GST) assay, and catalase (CAT) activity. In vivo therapeutic assessment is performed in Wistar Albino rats using vitamin C as a positive control. The livers and kidneys of individual animals are probed for glutathione, glutathione-S-transferase, and catalase activities. Seeds have GSH contents (59.61 µM) and leaves (32.87 µM) in the fresh aqueous extracts. The hydrogen peroxide scavenging effect of leaves is superior to seeds with 17.25% and 14.18% respectively after 30 min incubation. However, oxidatively stressed extracts with Ag(I) and Hg(II) show declining GSH and GST levels. The plant extracts are non-toxic in rats at 5000 mg/Kg body weight. Liver and kidneys homogenate reveal an increase in GSH, GST, and CAT levels after treatment with 150 ± 2 mg/kg and 300 ± 2 mg/kg body weight plant extract compared with normal saline-treated negative and vitamin C treated positive control. The crude aqueous extracts of leaves and seeds of plant DV show promising antioxidant potential both in in vitro and in vivo evaluation.